Cateter valvulado semi-implantavel para tratamento quimioterapico de longa duração: nova opção para utilização em quimioterapia venosa e arterial. - Albuquerque, Marcos Pires e (2023)
The authors present a catheter developed at the National Institute of Cancer, Rio de Janeiro, it has an anti-reflux device and serves to long-time chemotherapy, either venous or arterial. Indic tions and surgical implantation methods are discussed.